دراسة مقارنة وتحليل لأداء الآلات الافتراضية VMware Workstation.9 وVirtualBox.4 على جهازي حاسب مختلفين بالعتاد الصلب - سلمان تيسير (Latakia University Journal -Engineering Sciences Series, 2018)
This paper compares performance for two of the most used virtualization software VMworkstatio.9 and VirtualBox.4 on two separate computers with different hardware by making several tests on this two software to evaluate performance and obtain results based on chosen criteria and analyze results to reach conclusions on what virtualization software is the best and on what hardware it could be used. Results and measures showed that VirtualBox.4 performed better than VMware workstation.9. Hardware performance comparison gave precedence to the computer having hardware with high specifications. تقوم هذه الدراسة بمقارنة الأداء لبرنامجين افتراضيين VMware Workstation.9 وVirtualBox.4 وذلك على جهازي حاسب منفصلين ومختلفين من حيث العتاد الصلب من خلال إجراء عدة تجارب على هذين البرنامجين لتقييم الأداء بناءً على محددات تم اختيارها و تحليل النتائج للوصول الى استنتاجات حول أي برنامج هو الأفضل وعلى أي عتاد صلب يمكن اعتماده. أظهرت القياسات والنتائج أن البرنامج الافتراضي VirtualBox.4 أعطى أداء أفضل من البرنامج VMware Workstation.9 وذلك على كل من الحاسبين المستخدمين في الدراسة أما اختبارات العتاد الصلب أعطت أفضلية لجهاز الحاسب الذي يملك عتاد صلب بمواصفات أعلى.